Deprivation and late presentation of glaucoma: case-control study. Issue 7287 (17th March 2001) - Fraser, Scott; Bunce, Catey; Wormald, Richard; Brunner, Eric
Abstract: Objective: To identify socioeconomic risk factors for first presentation advanced glaucomatous visual field loss. Design: Hospital based case-control study with prospective identification of patients. Setting: Three hospital eye departments. Participants: Consecutive patients newly diagnosed with glaucoma (n=220). Cases (late presenters) were those presenting with advanced glaucoma (n=110), controls were those with early glaucoma (n=110). Results: Median underprivileged area scores were higher among late presenters (29.5; interquartile range 9.0-42.2) than in the control group (21.3; 6.1-37.4) (P=0.035). Late presenters were more likely to be of lower occupational class (odds ratio adjusted for age and referral centre 20.1 (95% confidence interval 2.6 to 155) for group III compared with group I-II and 86.0 (11.0 to 673 for group IV-V compared with group I-II), to have no access to a car (2.2; 1.2 to 4.0), to have left full time education at age 14 or less (7.5; 2.3 to 24.7), and to be tenants rather than owner occupiers (local authority tenants 3.2; 1.7 to 5.8, private tenants 2.1; 0.7 to 5.8). Effects of deprivation were partly accounted for by family history of glaucoma, time since last visit to an optometrist, and lack of an initial diagnosis of glaucoma by an optometrist. Conclusions: Area and individual level deprivation were both associated with late presentation of glaucoma. Existing evidence shows that late presentation is an important risk factor for subsequent blindness. Deprived groups thus seem to be at greater risk of going blind from glaucoma. Material deprivation may be associated with more aggressive disease as well as later presentation.